2006
DOI: 10.1007/s10725-005-5665-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auxins on Adventitious Root Development from Single Node Cuttings of Camellia sinensis (L.) Kuntze and Associated Biochemical Changes

Abstract: An attempt was made to induce rooting from single node cuttings of Camellia sinensis var. TV-20 under controlled conditions and study its biochemical changes during rooting. The nodal cuttings were pretreated with different concentrations of IAA, NAA and IBA and kept in a growth chamber (25 ±2°C, 16 h photoperiod (55 lmol m À2 s À1 ) with cool, white fluorescent lamps and 65% relative humidity) for 12 h. Among the three auxins used for pretreatment, IBA showed more positive response on rooting as compared to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 19 publications
6
66
0
8
Order By: Relevance
“…NAA produced less number of roots than IBA probably due to the reason that NAA accumulates and cannot be rapidly catabolized particularly at higher levels than that of IBA (Vuylsteker et al, 1997). In contrast to these results, Rout (2006) quoted that NAA promotes the number of roots by enhancing cell division in the root primordial.…”
Section: Root Number and Root Length (Cm)mentioning
confidence: 80%
“…NAA produced less number of roots than IBA probably due to the reason that NAA accumulates and cannot be rapidly catabolized particularly at higher levels than that of IBA (Vuylsteker et al, 1997). In contrast to these results, Rout (2006) quoted that NAA promotes the number of roots by enhancing cell division in the root primordial.…”
Section: Root Number and Root Length (Cm)mentioning
confidence: 80%
“…Applying IBA may have an indirect influence by enhancing the speed of translocation and movement of carbohydrates to the base of cuttings and consequently stimulate rooting (Davies et al 1990;Aminah et al 1995), so the rooting rate may be enhanced by the IBA treatment (Aminah et al 1995). This may also be related to total phenolic content and peroxidase activity, which are higher in IBA-treated cuttings, particularly during the initiation and expression phases (Moncousin and Gaspar 1983;Rout 2006). Similar to IBA, NAA treatment promotes rooting in conifer stem cuttings (Copes and Mandel 2000;Ragonezi et al 2010), but in the present study we found that NAA may be an inhibitor, which is in accordance with a study on apples (De Klerk et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…IAAO is an enzyme which catalyzes oxidation of IAA, or breaks down endogenous auxin (Hartmann, Kester, Davies Jr., & Geneve, 2010). The activity of POD is reported to be involved in an important step of root formation, during the metabolism of auxin and the process of lignification (Rout, 2006). PPO involved in metabolism of mono-and polyphenols during lignification process in plant cells (Khorsheduzzaman, Alam, Rahman, Mian, & Mian, 2010).…”
Section: Effectiveness Of Naa On Rootings Of Malay Applementioning
confidence: 99%